SISTEM PEMESANAN TREATMENT BERBASIS WEBSITE DI BEAUTY CLINIC PALEMBANG - Apriansyah; Tanjung, Alainaa Dewi (CV SWA Anugerah, 2024)
Beauty clinic is one of the beauty clinic businesses engaged in sales and care in the field of beauty. In the process of processing sales and treatment transaction recording data, it is still done by recording it in the transaction book. The researcher took the initiative to create a payment system and order treatment that could later be used by prospective customers and employees to record payment data. The research methodology used in this study is to use the waterfall method. Providing a website that makes it easy for prospective Beauty Clinic customers to view information related to the facilities provided and to make ordering and payment easier. The conclusion is that an information system has been compiled that is able to handle and make it easier for members and admins to access activities in the clinic.